Understanding why teachers entrust technology in innovating the learning outcomes - Sahlan Tampubolon; Lela Susanty; Khasanah Khasanah; Wisman Wisman; Agus Riyanto (Jurnal Konseling dan Pendidikan, 2021)
This study aims to analyze why elementary school and college educators trust technology to achieve teaching and learning outcomes. To discuss in order to answer the problem comprehensively and with high validity, we have collected data with the help of technology in a database of academic works such as journals, books, proceedings, magazines, and digital era educational technology websites. This study relies on secondary data with a phenomenological approach, exploring the broadest data often done in descriptive qualitative studies of social sciences and humanities. Examples of databases that we are targeting are the publications of Sagepub, Elsevier, Taylor & Francis, Google Books, and ERIC, which we specifically focus on for the latest issues between 2015 and 2021. Based on the data, findings and discussions can be summarized, between educators at both basic education levels until universities rely on ways to improve learning outcomes on the advantages and benefits of technology because of the effectiveness, innovation, and productivity of technology compared to teaching methods before the emergence of today's technology. The results of this study are expected to assist in the development of future technology and education studies.